Public preferences for government spending in Canada - Ramji Sabrina; Quiñonez Carlos (BMC, 2012)
Abstract This study considers three questions: 1. What are the Canadian public's prioritization preferences for new government spending on a range of public health-related goods outside the scope of the country's national system of health insurance? 2. How homogenous or heterogeneous is the Canadian public in terms of these preferences? 3. What factors are predictive of the Canadian public's preferences for new government spending? Data were collected in 2008 from a national random sample of Canadian adults through a telephone interview survey (n =1,005). Respondents were asked to rank five spending priorities in terms of their preference for new government spending. Bivariate and multivariable logistic regression analyses were conducted. As a first priority, Canadian adults prefer spending on child care (26.2%), followed by pharmacare (23.1%), dental care (20.8%), home care (17.2%), and vision care (12.7%). Sociodemographic characteristics predict spending preferences, based on the social position and needs of respondents. Policy leaders need to give fair consideration to public preferences in priority setting approaches in order to ensure that public health-related goods are distributed in a manner that best suits population needs.